The Study of Tandem Offloading Performance and Operability on The Cylindrical Hull FPSO Sevan Stabilized Platform with Variation in Mooring System Configuration - Eko Budi Djatmiko; Murdjito Murdjito; Jousie Rebecca (International Journal of Offshore and Coastal Engineering, 2017)
This study has been carried out to evaluate the dynamic behavior of the Cylindrical FPSO Sevan Stabilized Platform (SSP) and the LNG Carrier (LNGC) during the process of tandem offloading. The study includes hydrodynamics modellings, computations, and simulations of both cases SSP and LNGC operated individually and in combination for offloading operations. The SSP is moored with two variations of mooring, namely taut and catenary. Environmental loads are waves with the incorporated winds and currents propagating 90o, 210o, and 330o relative to the SSP headings. Excitation of random waves up to Hs = 4.50 m instigates the relatively low SSP motions in standalone condition. In offloading condition, when LNGC is connected, the SSP motion could magnify as much as 2.0 up to 5.0 times higher than that in standalone condition, but still considered in an acceptable level. The motion quality of LNGC in offloading operation is comparable with the SSP. For various random wave headings with Hs = 4.50 m during offloading operation may generate maximum tensions between 1,600 kN up to 2,600 kN in the casse of catenary mooring, and between 4,700 kN up to 7,000 kN in the case of taut mooring. Even then, this largest tension preserves a safety factor of 2.05 which is well above the limit of 1.67 as required by the governing standards. Finally, the study conclude an operability of as much as 90% could be achieved on SSP and LNGC offloading operation in the Masela Block of the Abadi Gas Field.